2018
DOI: 10.1139/facets-2017-0083
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the contribution of zoos and aquariums to peer-reviewed scientific research

Abstract: Modern zoos and aquariums aspire to contribute significantly to biodiversity conservation and research. For example, conservation research is a key accreditation criterion of the Association of Zoos and Aquariums (AZA). However, no studies to date have quantified this contribution. We assessed the research productivity of 228 AZA members using scientific publications indexed in the ISI Web of Science (WoS) database between 1993 and 2013 (inclusive). AZA members published 5175 peer-reviewed manuscripts over thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 34 publications
0
44
1
Order By: Relevance
“…Zoological databases that hold information on species' biology can enhance the scientific literature on natural history and ecology ; information that also informs animal management practices and species conservation strategies both in-situ and ex-situ. As centres for both pure and applied science, the output from zoological collections not only covers a range of disciplines (Loh et al 2018) but is of increasing value to multiple stakeholders working in all parts of the world with all taxonomic groups.…”
Section: Introductionmentioning
confidence: 99%
“…Zoological databases that hold information on species' biology can enhance the scientific literature on natural history and ecology ; information that also informs animal management practices and species conservation strategies both in-situ and ex-situ. As centres for both pure and applied science, the output from zoological collections not only covers a range of disciplines (Loh et al 2018) but is of increasing value to multiple stakeholders working in all parts of the world with all taxonomic groups.…”
Section: Introductionmentioning
confidence: 99%
“…Tse-Lynn Loh recently assessed the value of scientific zoological publications and found that not only do nonprofit zoos and aquariums publish scientific literature at significantly high rates, these publications are also highly cited by others. 1 Organizations with research-affiliated mission statements had the highest rates of output, as well as those with strong research funding and an established history of publication. This conservation research is a requirement for members of the Association of Zoos and Aquariums, and Loh determined that it contributes to broader ecological knowledge and conservation efforts.…”
Section: Scientific Zoological Publicationsmentioning
confidence: 99%
“…CAZA members participate in Species Survival Programs and captive breeding and reintroduction programs, while also collaborating with government and nongovernment organizations to preserve species in Canada and abroad (Galbraith and Rapley 2005). However, quantifying the contribution of zoos and aquariums to conservation-related activities is extremely difficult (Ferraro and Pattanayak 2006;Loh et al 2018). Research productivity in the form of peer-reviewed publications has been used to systematically quantify this contribution for members of the Association of Zoos and Aquariums (AZA), CAZA's counterpart in the United States (Loh et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, quantifying the contribution of zoos and aquariums to conservation-related activities is extremely difficult (Ferraro and Pattanayak 2006;Loh et al 2018). Research productivity in the form of peer-reviewed publications has been used to systematically quantify this contribution for members of the Association of Zoos and Aquariums (AZA), CAZA's counterpart in the United States (Loh et al 2018). Peer-reviewed publications are important contributions to scientific knowledge that can be shared with other practitioners and thus aid in the formulation of informed conservation management decisions (Loh et al 2018).…”
Section: Introductionmentioning
confidence: 99%